Application of Nave Bayes Algorithm for Security Performance Evaluation at PT. Sei Mangke Nusantara 3 - Handayani, Fifin; Sembiring, Rahmat W.; Saifullah (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2021)
Security serves as a security guard in an agency. In carrying out his duties a security must have a balance and functions in achieving the needs of an agency itself. In the world of work at an agency, especially security, which plays a role in maintaining the security of the agency. In the current era of security, there are those who are not responsible for their duties, so that an agency does not feel comfortable with the security. The purpose of this study to evaluate the performance of security at PT. Sei Mangke Nusantara Tiga and to create a safe and orderly atmosphere. In this study, the researchers used a Data Mining technique using the Naïve Bayes algorithm. Sources of research data obtained from the provision of questionnaires or questionnaires to danton PT. Sei Mangke Nusantara Tiga. The variables of the research used are discipline, attendance, honesty, communication skills and responsibility. In this study, the alternative used as a sample is security at PT. Sei Mangke Nusantara Tiga. The number of data tested is 5 security with two classes. From the results of the calculation of the Naïve Bayes Algorithm, it is obtained that there are 3 classes of good security and 2 security classes that are not good. The results of this study found that the level of accuracy of 100.00%.